Conductivity of Groundwater In Semarang City - Pinandita, Satria; Puji Lestari, Diah Aryati; Purwanti, Hani (Physics Communication, 2019)
Semarang is the capital of Central Java Province and is the most developed city in Java island. This city is one of the most important cities in the north coast of Java. Most of SemarangÃ¢â‚¬â„¢s landscape consists of lowland areas that become floodplain of the large rivers that flow through the city. Water is not only used for drinking but also for other necessities such as bathing, washing, agricultural and industrial needs, electricity generation, etc. The objective of this study was to determine the conductivity value of groundwater from several locations in Semarang as the conductor of electricity. This study used groundwater samples from seven locations in Semarang. The tests conducted including TDS (Total Dissolved Solid) test by inserting TDS meter into the water and recorded the value after 3 seconds of observation. The conductivity test was done by water electrolysis using a buzzer circuit. The test was conducted by inserting the electrode into the water for 3 seconds, then observed the buzzer sounding (soft or loud). Afterward, the water temperature was recorded using the thermometer. Results of this study showed the different water conductivity of groundwater collected from different locations. The lowest conductivity was obtained from S-1 sample with TDS value of 50 ppm, while the highest conductivity was obtained from S-7 sample with TDS value of 549 ppm. The higher the TDS and temperature value, the higher the electrical conductivity.Ã‚Â